IDENTIFIABILITY OF HIDDEN MARKOV MODELS - B. SETIAWATY (MILANG Journal of Mathematics and Its Applications, 2005)
This paper shows that the identiﬁability problem for hidden Markov models can be derived from the identiﬁability of ﬁnite mixtures.